2007
DOI: 10.1111/j.1460-9568.2007.05885.x
|View full text |Cite
|
Sign up to set email alerts
|

Slow oscillation of membrane currents mediated by glutamatergic inputs of rat somatosensory cortical neurons: in vivo patch‐clamp analysis

Abstract: Using in vivo patch-clamp technique, the slow oscillation of membrane currents was characterized by its synaptic nature, correlation with electroencephalogram (EEG) and responses to different anesthetic agents, in primary somatosensory cortex (SI) neurons in urethane-anesthetized rats. In more than 90% of the SI neurons, the slow oscillation of the inward currents (0.1-2.5 Hz) with the duration of several hundreds of a millisecond was observed at the holding membrane potential of -70 mV. The reversal potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…Soon after its description in anesthetized cats, it was shown during natural sleep in cats (Steriade et al, 1996; Amzica and Steriade, 1998) and in humans (Achermann and Borbély, 1997; Simon et al, 2000) and it has since been demonstrated in rodents (Cowan and Wilson, 1994; Petersen et al, 2003; Doi et al, 2007; Ruiz-Mejias et al, 2011). Subsequent investigations have shown it exists in nearly all sensory, motor and association areas of the cortex (Steriade et al, 1993c; Ferezou et al, 2006; Mohajerani et al, 2013) and synchronizes the membrane potential of cells in different functional regions far removed from each other (Destexhe et al, 1999; Volgushev et al, 2006; Dickson, 2010).…”
Section: Slow Wave Activitymentioning
confidence: 99%
“…Soon after its description in anesthetized cats, it was shown during natural sleep in cats (Steriade et al, 1996; Amzica and Steriade, 1998) and in humans (Achermann and Borbély, 1997; Simon et al, 2000) and it has since been demonstrated in rodents (Cowan and Wilson, 1994; Petersen et al, 2003; Doi et al, 2007; Ruiz-Mejias et al, 2011). Subsequent investigations have shown it exists in nearly all sensory, motor and association areas of the cortex (Steriade et al, 1993c; Ferezou et al, 2006; Mohajerani et al, 2013) and synchronizes the membrane potential of cells in different functional regions far removed from each other (Destexhe et al, 1999; Volgushev et al, 2006; Dickson, 2010).…”
Section: Slow Wave Activitymentioning
confidence: 99%
“…Recently, the in vivo whole-cell patch-clamp recording technique has been applied to rat somatosensory cortical neurons (Doi et al, 2007). Recording neurons, which respond to brush or pinch stimulation of contralateral hind limb, were located between 0.5 and 1.0 mm in the depth from the brain surface (Doi et al, 2007), suggesting that these neurons are largely layer V pyramidal neurons. Taking these findings into consideration, we then looked at the influence of deleting GAD65 gene on spontaneous GABAergic synaptic currents in sensory cortical neurons (layer V).…”
Section: Thermal Hyperalgesia In Gad65 Knockout Mice 165mentioning
confidence: 99%
“…Layer V pyramidal neurons receive thalamic input from the main specific sensory relay the ventral posteromedial nucleus and as such are considered to function within the sensory pathway (Deschênes et al, 1994). Recently, the in vivo whole-cell patch-clamp recording technique has been applied to rat somatosensory cortical neurons (Doi et al, 2007). Recording neurons, which respond to brush or pinch stimulation of contralateral hind limb, were located between 0.5 and 1.0 mm in the depth from the brain surface (Doi et al, 2007), suggesting that these neurons are largely layer V pyramidal neurons.…”
Section: Thermal Hyperalgesia In Gad65 Knockout Mice 165mentioning
confidence: 99%
“…Urethane anesthesia creates a state of delta-wave activity where the EEG fluctuates at 0.5–4 Hz due to the burst-pause activity of L5 neurons, similar to the condition present in natural slow-wave sleep (Armstrong-James et al 1985; Armstrong-James and Fox 1988). The burst activity is generated partly by intracortical circuits, particularly via horizontal connections in L5 (Beltramo et al 2013; Chauvette et al 2010; Le Bon-Jego and Yuste 2007), and partly by thalamic input originating in principal and intralaminar thalamic nuclei (David et al 2013; Doi et al 2007; Fox and Armstrong-James 1986). The decrease in spontaneous activity in the L5RS cells was accompanied by a hyperpolarization in membrane potential, suggesting a decrease in excitatory drive.…”
Section: Discussionmentioning
confidence: 99%